Development of functionalised zeolite and bentonite for the recovery of platinum group elements (PGEs) and rare earth elements (REEs) from aqueous systems impacted by mining activities - Mosai, Alseno Kagiso (My University, 2021)
The economies of many countries, including South Africa, have been highly dependent on mining activities. Infrastructure including roads, buildings and power supplies has been improved over the years due to mining. As such, minerals such as gold, platinum group elements (PGEs), rare earth elements (REEs) and diamond continue to be mined, and their value increasing as demand outpaces supply due to diminishing resources. This has led to an increase in recycling efforts to salvage these precious elements. However, not much attention has been paid to deriving value from waste streams emanating from processing plants and discharged into the environment. To this end, the focus of this study was to use functionalised zeolite and bentonite as adsorbents for the recovery of PGEs and REEs from aqueous solutions of the type discharged from mineral processing plants. The research approach involved functionalising zeolite and bentonite with nitrogen containing ligands, namely: hydrazine, 3-aminopropyl(diethoxy)methylsilane (APDEMS) and spent yeast. These ligands were used because PGEs have been found to have strong interactions with nitrogen therefore, functional groups containing amine groups were ideal for functionalisation. Moreover, the stability constants between PGEs and nitrogen are very high (log k >10). The functionalised adsorbents were characterised using: Fourier transform infrared spectroscopy (FTIR) to determine functional groups; X-ray fluorescence (XRF) to determine the elemental composition; powder X-ray diffraction (PXRD) to determine the mineralogy; scanning electron microscope (SEM) to determine surface morphology; and elemental analyser to determine the extent of anchoring of the iv ligands. Textural properties (surface area, pore size and pore volume) were determined using Brunauer–Emmett–Teller (BET) for surface area analysis. The performance of the adsorbents in batch experiments was assessed by studying the effects of: pH; adsorbent dosage; initial concentration; contact time; and competing ions (Fe(III), Ca(II), Mg(II), K(I), Co(II), Ni(II), Hf(IV), Au(I), Zn(II) and other PGEs). Column studies were also conducted to assess the performance of the adsorbents under dynamic conditions. The effects of adsorbent bed height, pH, flow rate and initial concentration were investigated. Experimental results for both batch and column modes were assessed using various models. Adsorption capacity and efficiency models were used to determine the performance of adsorbents. Two-parameter (Langmuir, Freundlich, Dubinin-Radushkevich and Temkin) and three-parameter (Sips, Redlich-Peterson and Toth) isotherm models were used to determine the relationship between adsorbed elements and adsorbents. The adsorption mechanism was investigated using pseudo first-order, pseudo second-order, Elovich and intra-particle diffusion kinetic models. The performance of adsorbents in column mode was determined using column models such as Adams Bohart, Thomas, Yoon-Nelson, Clark, Wolborska, bed depth service time and modified dose response model. A generalised surface complexation model based on coupling parameter estimation (PEST) and the PHREEQC geochemical modelling code was used to obtain further insight into the adsorption mechanism. The model was calibrated using results from laboratory experiments. The findings showed that zeolite and bentonite in their natural forms had low adsorption efficiency (<5%) for PGE removal. However, after functionalising the materials with hydrazine, APDEMS or spent yeast, the uptake significantly increased (p <0.05), due to strong interactions between amine groups and the elements. Functionalisation of the v adsorbents was confirmed by FTIR and the elemental analyser. The surface area of bentonite was found to be higher than that of zeolite, resulting in the anchoring of more amine groups onto the former. The recovery of PGEs (Pt(IV), Pd(II) and Ir(III)) was highest at pH 2 and, significantly (p <0.05), decreased at pH >2, due to changing speciation and surface charge. However, the recovery of Rh(III) was efficient at pH ≥5 since, the Rh(III) species become positively charged with increasing pH, making them to be attracted to the negatively charged adsorbent surface. The adsorbents were highly efficient when concentrations of PGEs were low (2 mg L-1 ), with an adsorbent dosage of 10 g L-1 . The results also indicated that 90 min of contact was optimal for maximum adsorption of PGEs. The highest adsorption efficiency was >98, >98 and >95% for Pt(IV), Pd(II) and Ir(III), respectively, when functionalised bentonite was used and, >76, >91 and >60% for Pt(IV), Pd(II) and Ir(III), respectively, when functionalised zeolite was used. The uptake of the elements increased in the presence of competing ions, likely due to synergistic effects. The Langmuir isotherm model best fitted the adsorption data, indicating that the elements were only attracted to active sites with similar energies (i.e. - NH2 groups). The adsorption mechanism was described by the pseudo second-order kinetic model which is associated with adsorption via strong chemical interaction. The recovery of REEs was efficient when both the natural and functionalised adsorbents were used, but the natural adsorbents were used since their adsorption capacities were higher. The uptake of REEs was high (>98%) when bentonite was used at different solution conditions (pH> 2, concentration (0.5 – 10 mg L-1 ) and adsorbent dosage (5 – 50 mg L-1 )). However, the maximum uptake of REEs using zeolite was only achieved when the concentration was 2 mg L-1 or less, at pH >5 and adsorbent dosage of 10 g L-1 . The high uptake of REEs by natural zeolite and bentonite was attributed to the negative vi structural charge of the adsorbents over a wide range of pH, including acidic pH. Moreover, PHREEQC geochemical modelling code indicated that all REEs are positively charged even in solutions with pH >7. Thus, the adsorbents were always in favourable conditions for the adsorption of REEs. The high surface areas of the adsorbents also played a major role on the uptake of the elements. In contrast, the functionalised zeolite and bentonite had lower surface areas compared to their natural counterparts and the uptake was low at highly acidic pH solutions since the structural surface charges of the adsorbents were positive. The adsorption of most REEs (e.g. Y, Pr) onto bentonite was described by the Langmuir isotherm model and some (e.g. Ce, Gd, Tm) by the Freundlich model. Thus, most of the REEs adsorbed onto active sites with similar energies but some onto different active sites with different energies. The adsorption of all REEs onto zeolite was described by the Langmuir isotherm. Adsorption mechanism of REEs was described by the pseudo second-order kinetic model. Breakthrough curves from column studies indicated that the uptake of PGEs and REEs increases with increasing bed height due to a higher number of binding sites. Higher flow rates (>2 mL min-1 ) do not give the elements enough time (residence time) to interact with the adsorbents therefore, breakthrough times were observed earlier than when lower flow rates were used. Agreement of experimental and modelled data (p >0.05) indicated that the coupling of PHREEQC to PEST can be used to determine the efficiency of the adsorbents on the recovery of precious elements when necessary conditions such as pH, concentration and surface area are determined and used for the calibration of the PHREEQC model. Also, it was observed that only a few experiments were required for this purpose. vii Indicative cost-benefit analyses showed that the efficient uptake of PGEs and REEs by amine-functionalised and natural adsorbents, respectively, implied that these elements could be potentially recovered from wastewaters. For instance, up to 25 ounces of Pt per kg of yeast-functionalised bentonite and 54 ounces of REEs per kg of natural bentonite could be recovered, which are higher recoveries compared to amounts cited for economical mining. This could be important even for low level concentrations in waste streams as companies seek to salvage these metals from sundry sources to make up for increasing costs, declining natural resources and increasing demand. The successful coupling of PHREEQC and PEST suggests that limited experimental data can potentially be used to do predictions of sorption processes in generalised surfaces such as those studied here. Upon successful calibration, complex reactions and time consuming experiments can be simulated. This procedure can potentially be used by mining companies and other industries as a preliminary step to determine the feasibility of administering adsorbents to recover elements from wastewaters. The use of PHREEQC coupled to PEST for simultaneous recovery of REEs using a generalised surface could not be done but, would be important for future studies. Such studies should also focus on the recovery of elements in the presence of organic compounds such as low molecular weight humic and fulvic acids.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2021